Affectivity in interaction [ sound objects in English - Reber, Elisabeth (Pragmatics & beyond new series, 2012)
How do participants display affectivity in social interaction? Presenting an in-depth analysis of a little researched area of language use from an interactional linguistic perspective, the book is of theoretical and methodological interest to an audience with a background in linguistics, sociology and conversational studies